CAPITAL STRUCTURE AND FINANCIAL PERFORMANCE OF QUOTED MANUFACTURING FIRMS IN NIGERIA - Elizabeth Omolehin, Motunrayo; Joseph Inyada, Sunday; Alapo, Tope (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2020)
Decision about combination of various sources of finance that can maximize a firm’s overall value which means optimal capital structure is pivotal to the performance and survival of same. This type of decision of determining the exact optimum capital structure however is not an easy one. The objective of the study was to determine the effect of capital structure (proxy by debt equity ratio) on the financial performance of quoted manufacturing firms in Nigeria. Data were sourced from the sampled firms' annual reports over the study period of 2008-2018 and analyzed using the generalized least square regression technique. The study found out that the use of more debt compared to equity has significant positive effect on the financial performance of quoted manufacturing firms in Nigeria. The study recommends that manufacturing companies increase their debt-to-equity ratio and Government should stimulate financial institutions so as to be debt friendly to these firms.